Genarchopsis dasus and Camallanus anabantis parasites of Channa punctatus from Dinajpur Region of Bangladesh (Research in Agriculture Livestock and Fisheries, 2024)
This study was conducted to identify seasonal infestations of parasites in Channa punctatus of Dinajpur, Bangladesh. Sampling was carried out frequently over a year in selected cultural and natural sources. A total of 120 fish was examined among them 32 fishes were infested and collected parasites were 72. Two parasites were recorded, Genarchopsisdasus and Camallanusanabantis. The prevalence was found 26.67 % and mean intensity 2.41. The maximum prevalence was found in August (50 %) and the lowest in December, January, February (10 %). The maximum mean intensity was January (8) and the lowest was December and June (1). The highest prevalence (40 %) was observed in winter and the lowest (10 %) was in the rainy season. The maximum prevalence (50 %) was recorded in male fish in summer and autumn. However, the mean intensity (6.5), index of infection (3.71), and abundance (1.85) were highest in female fishes. The prevalence (30.23 %), abundance (0.74), and index of infection (0.68) were observed maximum in smaller size group and the lowest in large size group (24.44 %, 0.38 %, and 4.16 respectively). There was a variation of infestation of fish according to length, sex, season, and sources.Vol. 10, No. 3, December 2023: 367-376